Dual enzyme responsive resorufin-based type-I/II photosensitizer for selective treatment of neuroblastoma cells under hypoxia - Koçak, Haluk; Kilcan, Zeynep; Zhang, Pengfei; Almammadov, Toghrul; Kolemen, Safacan (Sensors and actuators. B, Chemical, 2026)
Designing highly selective photosensitizers (PSs) that exhibit no photocytotoxicity toward normal cells is a defining feature of next generation photodynamic therapy (PDT) agents. Activity-based PSs, which become photocytotoxic only upon activation by a tumor-associated analyte, hold great promise in this regard. However, those responsive to a single analyte often face challenges in achieving sufficient selectivity. To overcome this limitation, dual analyte responsive (dual-locked) PSs offer significant potential to enhance cancer-cell specificity. Nevertheless, dual-locked PDT agents engaging both PDT mechanisms, remain rare. In this study, we report a dual enzyme responsive photosensitizer (RAM) based on an iodo-resorufin scaffold for highly selective type-I/II PDT. RAM is designed to be sequentially activated by two tumor-associated enzymes, aminopeptidase N (APN) and monoamine oxidase (MAO), thereby implementing an enzyme-induced AND logic activation mechanism to achieve enhanced selectivity toward cancer cells. RAM remains inactive in normal cells. Upon activation in cancer cells, RAM generates both singlet oxygen and type-I radicals, including superoxide anion and hydroxyl radicals, thus combining the advantages of both PDT mechanisms. In neuroblastoma 2D and 3D models, RAM demonstrates potent and selective phototoxicity toward cancer cells, as well as effective cell killing under hypoxic (1% O2) conditions. This dual-locked, dual-mode approach achieves unprecedented specificity and efficacy in PDT, offering a promising strategy to minimize off-target effects and extend therapeutic applicability to aggressive, hypoxic tumors. Notably, this study reveals, for the first time, the type-I PDT potential of the iodinated resorufin core, opening new avenues for the development of activity-based, dual-locked type-I/II PDT agents.
Online verfügbar: 5. November 2025, Artikelversion: 8. November 2025
Gesehen am 28.01.2026